PERAN DAN FUNGSI KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) KOTA MAKASSAR DALAM MENCIPTAKAN PERSAINGAN USAHA YANG SEHAT TINJAUAN SIYASAH SYAR’IYYAH - Sukardi, Fikri Abdillah; Tenripadang, Andi; Syarif, Muh. Rasywan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
KPPU is an independent institution, which in handling, deciding or conducting an investigation of a case cannot be influenced by any party, both the government and other parties who haveConflik of Interest, even though in carrying out its powers and duties it is responsible to the President. KPPU is also an institutionQuast Judiciary having executive authority in relation to business competition cases. Makassar KPPU stopped the case of alleged business monopoly in the Makassar sea sand mining project because it was deemed not to have fulfilled the completeness and clarity of the report as stipulated in KPPU regulation No.1/2019. The five pieces of evidence referred to in the regulation are witnesses, documentary evidence, expert testimony, instructions and statements of the reported party. Meanwhile, the reporting party, the Save the Indonesian Sea Coalition (KSLI), was assisted by the Makassar Legal Aid Institute (LBH). The main problem in this study is how the Role and Function of the Makassar City Business Competition Supervisory Commission (KPPU) in creating fair business competition according to Siyasah Syar'iyyah's review. The type of research used is field qualitative (field reseasch). Based on the results of this study, it shows that in an effort to create fair business competition in Makassar City, the Business Competition Supervisory Commission (KPPU) has taken several preventive measures, namely carrying out socialization so that the public can find out and monitor the activities of business actors, hold hearings with several business actors, conduct Advocacy on government policies and activities of business actors in market competition, KPPU holds journalist forums with various media that work together to socialize unfair business competition, holds discussion forums with academics such as public lectures on campuses, conducts policy advocacy to the government that has the potential to result in practices monopoly and unfair business competition, assess agreements that may result in unfair business competition, and supervise companies in Makassar City.